Caregivers as a proxy for responses of dementia clients in a GPS technology acceptance study (2018)
Objective: The objective of this study was to examine the extent to which caregivers can be used to provide proxy responses for dementia clients in a study on the acceptance of GPS technology. Methods: Forty-five client–caregiver dyads used one of three GPS devices. The Unified Theory of Acceptance and Use of Technology (UTAUT) was used to create two questionnaires, one for dementia clients and one for caregivers, as proxies. Spearman rho bivariate correlations of responses for each UTAUT construct were used to compare the client and caregiver responses post-usage of the GPS devices. Results: The mean age of the clients was 76.02 years (SD = 11.5). Overall, after using the GPS devices, the responses of the clients and caregivers were correlated and statistically significant (rxy Overall summative scale = 0.550). In addition, 4 out of 6 constructs of the UTAUT were correlated and statistically significant (p and lt; 0.05) (rxy Performance Expectancy = 0.160; rxy Social Influence = 0.478; rxy Behavioural Intention to Use = 0.347; and rxy Actual Use = 0.570). Conclusion: The degree of agreement between the caregivers and clients, especially for the constructs intention to use and actual use of the GPS technology, suggested that caregivers can respond on behalf of dementia clients on technology acceptance questionnaires. © 2018 Informa UK Limited, trading as Taylor and Francis Group.